The Development of Strontium Titanate Nanoparticle Research: A Bibliometric Computational Mapping Analysis - Nainggolan, Yohanes Ivan Benaya Parlindungan; Nandiyanto, Asep Bayu Dani (Penerbit Goodwood, 2025)
bibliometric approach and also using computational mapping analysis using VOSviewer. Methodology: The keyword “SrTiO3 nanoparticle, Strontium Titanate” is used, then the article is selected based on the title and abstract. We conducted an analysis of articles discussing SrTiO3 nanoparticles and their relationship to problem areas using VOSviewer.Results/findings: A total of 667 relevant articles were found based on these keywords. Articles used in the last 11 years, from 2012 to 2022. The results showed that SrTiO3 nanoparticles can be divided into 3 fields: “SrTiO3” with 163 links and 1092 total link strength, “Nanoparticle” with 175 links and 1697 total link strength, and “Strontium Titanate” with 170 links and 1459 total link strength. It was found that the research trend of SrTiO3 nanoparticles was increasing. In 2012 to 2015 there was an increase from 29 articles in 2012 to 46 articles in 2015. There was a decrease from 2015 to 40 articles in 2016. From 2016 to 2022 there was a significant increase in the number of articles from 40 articles in 2016 to 93 articles in 2022. Conclusion: The bibliometric and mapping analysis revealed that research on SrTiO3 nanoparticles continues to grow rapidly, with strong interdisciplinary linkages across materials science, energy, and nanotechnology. This indicates that SrTiO3 nanoparticles have promising potential for future innovations, especially in energy conversion, photocatalysis, and electronic device applications.Limitations: This study did not discuss in depth the relationship between the terms in this SrTiO3 nanoparticle study.Contribution: The results of this study can be used as a reference to find out the trend of research on nanoparticle materials which has increased, so that it can be a potential for further development of SrTiO3 nanoparticle applications.